Investigating the Existence of a Cathode Electrolyte Interphase on Graphite in Dual‐Ion Batteries with LiPF6‐Based Aprotic Electrolytes and Unraveling the Origin of Capacity Fade - Lukas Haneke; Felix Pfeiffer; Katharina Rudolf; Pranti Sutar; Masoud Baghernejad; Martin Winter; Tobias Placke; Johannes Kasnatscheew (Advanced Energy & Sustainability Research)
This study elucidates the presence of a cathode electrolyte interphase (CEI) at graphite positive electrodes (PEs) and assesses its impact on the performance of dual‐ion batteries, being promising candidates for cost‐efficient and sustainable stationary energy storage. Indeed, electrolyte oxidation increases during charge (5 V vs Li|Li+) for decreased C rates, that is longer duration at high state‐of‐charges (SOC) , but effective protection and evidence for CEI formation is missing as no increase in Coulombic efficiencies is observed, even with literature‐known electrolyte additives like vinylene carbonate, fluoroethylene carbonate, or ethylene sulfite in a highly concentrated base electrolyte (4.0 m LiPF6 in dimethyl carbonate) as reference. Via studying charged and pristine PEs by X‐ray photoelectron spectroscopy, PF6−‐graphite intercalation compounds and cointercalated solvent molecules are identified, while indications for CEI are absent within 1000 charge/discharge cycles. Nevertheless, a high capacity retention of ≈94% (referring to 0.1C) is demonstrated. Affirmed by Raman spectroscopy and scanning electron microscopy, the active material remains structurally stable, suggesting capacity fading to be dominated by resistance rise at the PE, likely due to an electronic contact resistance from active material grain boundaries and/or from the interface between electrode particles and the current collector in course of high volume changes; as systematically derived by impedance spectroscopy.